2001
DOI: 10.1023/a:1012244520615
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The serum concentration of digoxin after single oral administration was lower in the subjects harboring a mutant allele (C3435T) at exon 26 of the MDR1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 286 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…3). 57) This result agreed with our results on MDR1 mRNA levels in the biopsy specimens of duodenum (Fig. 1).…”
Section: )supporting
confidence: 93%
See 1 more Smart Citation
“…3). 57) This result agreed with our results on MDR1 mRNA levels in the biopsy specimens of duodenum (Fig. 1).…”
Section: )supporting
confidence: 93%
“…Interethnic differences in allele and genotype frequencies of C3435T are summarized in Table 3. [53][54][55][56][57] Few homozygotes for the T-allele (T/T 3435 ) were found with about 80% of individuals homozygotic for the C-allele (C/C 3435 ) in Ghanaian, Kenyan, African American and Sudanese populations, whereas T-allele frequencies were almost 50% for Caucasians and Asians.…”
Section: Mdr1mentioning
confidence: 99%
“…16,17) The genotypes of T-129C, G2677A,T and C3435T of the MDR1 gene were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis as described before 16,17) and confirmed by direct sequencing. Herein, C1236T was also determined by direct sequencing according to the report by Kim et al 18) The gene product of MDR1 is the multi-drug resistant transporter MDR1/P-glycoprotein, a glycosylated membrane protein of 170 kDa, belonging to the ATP-binding cassette superfamily of membrane transporters.…”
Section: Steroid Therapy For Relapses Of Ns or Slementioning
confidence: 99%
“…24) Greiner et al reported that the expression level of the MDR1 gene affects the plasma clearance of digoxin after oral administration. 25) Furthermore, Goto et al suggests that the MDR1 C3435T polymorphism correlates with the intestinal expression level of CYP3A4.…”
Section: Subjects and Study Protocolsmentioning
confidence: 99%
“…25) Assay of Carvedilol The blood concentration of carvedilol was measured using chiral high performance liquid chromatography (HPLC) as described by Mihara et al with minor modifications. 8,27) Briefly, whole blood samples (0.2 ml) were mixed with 0.5 ml of distilled water to hemolyze the blood cells.…”
Section: Subjects and Study Protocolsmentioning
confidence: 99%